(untitled) (Research, Society and Development, 2021)
Malnutrition in hospitalized patients correlates with the increased frequency of clinical complications and mortality, in addition to being associated with a longer period of hospitalization, greater risk of infections and increased costs for the health service. The objective of this research was to elaborate a systematic review on the effect of nutritional assessment on the length of hospital stay and to characterize the prevalence of malnutrition and nutritional risk in hospitalized patients. A systematic review of original articles was carried out using the descriptors "Nutrition Assessment", "Length of stay" and "Prognosis", in the Bireme / VHL databases, published in English, Portuguese or Spanish. Of a total of 2,181 patients analyzed in the selected studies, about 57% were aged 60 years or over, with an average ranging between 63 and 85 years. The prevalence of malnutrition or nutritional risk in the general population studied ranged from 0.98% to 69.9%, depending on the nutritional assessment instrument used in the analysis. Regarding the length of hospital stay and its association with the degree of malnutrition or nutritional risk, there was a positive correlation in most of the series. The high prevalence of malnutrition at hospital admission seems to lead to longer hospital stays for patients, higher hospital costs and worse clinical outcome. Although there is no adequate nutritional assessment model, its importance is indisputable and further studies are needed to better elucidate the topic.